PENERAPAN MESIN PENGIRIS SINGKONG PADA INDUSTRI KECIL KRIPIK SINGKONG - IG.A.K. Suriadi; I D. G. A. Subagia; I K. A. Atmika (Buletin Udayana Mengabdi, 2016)
The Negara city is an area that has already quite crowded, shown by the availability of many facilities, sosmall industrial/business group are emerging, one of which is an industry or group of enterprises manufactureof cassava chips "Niki Suka". Meanwhile, in the eastern region of of Bali island, there are UD. Gurih Sari, isa small industry that produces cassava chips as well . Production of chips is still utilizing local resourcesandproduced conventionally. UD Gurih Sari and Suka Niki Suka business groups, both have a similarproblem that is related to productivity, caused by small capacity and conventional of cassava cutlery/slicer, aswell as low educational background of human resources (HR). The aims of the activity is to generate cassavaslicing/cutting machine. Solutions or methods offered in this program is to replace the equipment or theconventional way with a cassava mower/slicer. Technical planning activities of our team was using someinput from business groups partner. The next activity in introducing the good management "of the company "that was dealed and desired by the partner. Then continued by the introcudtion of work safety. The firstcommunity service activities held on August 22, 2015 at Niki Suka women business group, located in thevillage Cupel, Negara, Jembrana District, Bali. The activities began with a demo making cassava chipsconventionally by Niki Suka women business group, continued by introducing and demonstrating themachine that we made. This training can improve the skills of the workforce in producing cassava chips.